Frequency-dependent dielectric spectroscopic analysis on phytochemical and antioxidant activities in Radix Glycyrrhizae extract - Hong Liang, Ong; Ee Meng, Cheng; Mohamad, Che Wan Sharifah Robiah; Mohd Nasir, Nashrul Fazli; Xiao Jian, Tan; Chong You, Beh; Ziezie Mohd Tarmizi, Emma; Kim Yee, Lee; Kok Yeow, You; Shing Fhan, Khor; Kim Fey, Leu; Kian Keong, Te; et al. (Elsevier, 2024)
Radix Glycyrrhizae, the dried roots of the Glycyrrhiza glabra plant, is a popular Chinese herbal medicine known for its various health benefits. It is particularly effective in relieving respiratory problems like coughs, sore throats, bronchitis, and asthma. However, there is limited research on the electrical properties of Radix Glycyrrhizae, likely due to its complex composition of phytochemical and antioxidant activities. This research aims to investigate the potential of these active biological compounds and understand their electrochemical properties. In this study, High-Performance Liquid Chromatography (HPLC) analysis revealed that Radix Glycyrrhizae decoction contains significant amounts of flavonoids and saponins, compounds known for their health benefits and therapeutic effects. Further analysis using Fourier Transform Infrared Spectroscopy (FTIR) identified several functional groups, including phenols, alcohols, alkynes, alkenes, ethers, and glycosides, which contribute to the plant's medicinal potential and affect the impedance and dielectric properties of the extract. The antioxidant activity of Radix Glycyrrhizae decoction was also evaluated using DPPH assays, showing similar radical scavenging activity to gallic acid. Dielectric and impedance measurement of Radix Glycyrrhizae extract were performed using an Agilent vector network analyzer and a Hioki impedance analyzer. The dielectric constant measured was consistent across both analyzers. However, the loss factor showed different trends: the vector network analyzer indicated a decrease in the loss factor with increasing frequency in the range of 5 MHz–20 GHz, while the impedance analyzer showed the opposite trend in the frequency range of 4 Hz–5 MHz.